2015
DOI: 10.1139/cjpp-2015-0105
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxins in cardiovascular disease

Abstract: Key thioredoxin (Trx) system components are nicotinamide adenine dinucleotide phosphate (NADPH), Trx reductase (TrxR), and Trx. TrxR catalyzes disulfide reduction in Trx with NADPH as cofactor. Because Trx is an antioxidant, oxidative stress results in an increase in Trx, which has a reduced disulfide component. If Trx is suppressed, oxidative stress in higher.In contrast a decrease in oxidative stress is associated with low Trx levels. Trx is involved in inflammation, apoptosis, embryogenesis, and cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…In AD, formation of beta amyloid plaques can induce oxidative damage to neurons via formation of H 2 O 2 , which is decomposed to the highly reactive hydroxyl (OH) radical in presence of Fe 2+ (Su et al, ; Whayne, Parinandi, & Maulik, ). More critical is the brain being highly susceptible to free radical attacks due to their rich content of polyunsaturated fatty acids, which are easily oxidized (Adefegha et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In AD, formation of beta amyloid plaques can induce oxidative damage to neurons via formation of H 2 O 2 , which is decomposed to the highly reactive hydroxyl (OH) radical in presence of Fe 2+ (Su et al, ; Whayne, Parinandi, & Maulik, ). More critical is the brain being highly susceptible to free radical attacks due to their rich content of polyunsaturated fatty acids, which are easily oxidized (Adefegha et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that decreased thiol levels may be an underlying pathophysiologic cause for development of CAD, and thus we speculate that our study can inspire the future studies about development of new treatment strategies so as to treat CAD. We hope that some molecules such as gamma-glutamylcysteine-ethyl-ester or thioredoxins affecting thiol levels or activity might provide a useful alternative to conventional medications for the prevention and treatment of CADs in near future [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…SFN has been shown to inhibit ECs proliferation via apoptosis and autophagy (27)(28)(29) and suppress VEGF and MMP-2 expression (30,31), the latter being associated with the inhibition of FOXO1/AKT pathways (32). Moreover, SFN is a known inducer of both thioredoxin reductase (TrxR1) and thioredoxin (26,33), which are involved in inflammation, apoptosis, angiogenesis, embryogenesis and cardiovascular disease involved in angiogenesis (34). The molecular mechanisms of SFN suppression of angiogenesis, in particular the effects on signalling pathways between ECs and pericytes in response to SFN treatment, are not fully understood.…”
Section: Introductionmentioning
confidence: 99%